Electrophysiologic studies in leprosy - Joaquim P. Brasil-Neto (Arquivos de Neuro-Psiquiatria)
The author reviews the literature on electromyography and nerve conduction velocity studies in leprosy. It is concluded that these studies can be helpful in the early diagnosis of neural involvement, in the elucidation of pathophysiological mechanisms, and in the follow-up of patients under medical and/or surgical treatment.